2005
DOI: 10.1023/b:drug.0000047101.02178.07
|View full text |Cite
|
Sign up to set email alerts
|

Possible synergistic prostate cancer suppression by anatomically discrete pomegranate fractions

Abstract: We investigated whether dissimilar biochemical fractions originating in anatomically discrete sections of the pomegranate (Punica granatum) fruit might act synergistically against proliferation, metastatic potential, and phosholipase A2 (PLA2) expression of human prostate cancer cells in vitro . Proliferation of DU 145 human prostate cancer cells was measured following treatment with a range of therapeutically active doses of fermented pomegranate juice polyphenols (W) and sub-therapeutic doses of either pomeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 46 publications
3
111
0
6
Order By: Relevance
“…Supraadditive, complementary and synergistic effects were proven in all models. Lansky et al (2005b) found equally combined amounts of pomegranate fermented juice, pomegranate pulp juice, cold-pressed pomegranate seed oil extracts resulted in a 99% suppression of DU-145 prostate cancer cell invasion across a matrigel matrix. Ellagic acid, caffeic acid, luteolin and punicic acid, important components of pomegranate significantly inhibited in vitro invasion of human PC-3 prostate cancer cells when employed individually.…”
Section: Prevention Of Prostate Cancermentioning
confidence: 93%
“…Supraadditive, complementary and synergistic effects were proven in all models. Lansky et al (2005b) found equally combined amounts of pomegranate fermented juice, pomegranate pulp juice, cold-pressed pomegranate seed oil extracts resulted in a 99% suppression of DU-145 prostate cancer cell invasion across a matrigel matrix. Ellagic acid, caffeic acid, luteolin and punicic acid, important components of pomegranate significantly inhibited in vitro invasion of human PC-3 prostate cancer cells when employed individually.…”
Section: Prevention Of Prostate Cancermentioning
confidence: 93%
“…(2004) udowodnili, że zarówno olej z nasion granatu, jak i fermentowany sok z owocu hamują proliferację komórek raka gruczołu krokowego (LNCaP, PC-3, DU-145). Zauważono także, że ekstrakty z całych owoców granatu są bardziej skuteczne w działaniu antynowotworowym aniżeli ekstrakty przygotowane z poszczególnych części owocu (Lansky i in., 2005). Dwa dostępne badania sugerują, że u podstaw mechanizmu hamowania wzrostu komórek linii PC-3 leży modulowanie białek regulujących procesy apoptozy (Malik i in., 2005;Malik i Mukhtar, 2006).…”
Section: Właściwości Przeciwnowotworoweunclassified
“…Pomegranate ellagitannins have been shown to inhibit PCa cell proliferation in vitro and human PCa xenograft growth in vivo (18)(19)(20). The most abundant ellagitannin in pomegranate juice is called punicalagin.…”
Section: Introductionmentioning
confidence: 99%